THE EFFECT OF ADDITIONAL EGGS SHELL FLOUR IN FEED ON THE CARCASSES COMPOSITION OF 10 WEEKS QUAIL - M. M., Rano; Candrawati, D.P.M.A.; Wirapartha, M. (Jurnal Peternakan Tropika, 2023)
This study aimed to determine the effect of adding eggshell flour in the ration on the physical composition of quail carcasses aged 10 weeks, carried out at the Unud Pasraman Housing, Block F-30 and the Poultry Livestock Laboratory, Faculty of Animal Husbandry, Udayana University, for 4 weeks. The study used a completely randomized design (CRD), with 4 treatments and 4 replications, each replication using 4 quails ( Coturnix-coturnix japonica ). The ration treatment consisted of: P0: Without the addition of eggshell flour in the ration; P1: addition of 4% eggshell flour in the ration; P2: addition of 6% eggshell flour in the ration; P3: addition of 8% eggshell flour in the ration. The variables observed included slaughter weight, carcass weight, carcass percentage, and carcass physical composition (percentage of meat, percentage of bone, percentage of fat including skin). Coturnix-coturnix japonica that were given the addition of 4% (P1), 6% (P2), and 8% (P3) eggshell flour in the diet was significantly (P<0.05) higher than that of eggshell flour. control (P0). Carcass weight had a significant effect (P<0.05) compared to the control treatment (P0). The carcass percentage had a significant effect (P<0.05) compared to the control treatment (P0). Carcass physical composition (percentage of meat) had a significant effect (P<0.05) compared to the control treatment (P0). Bone percentage and fat percentage including quail skin treatment P1, P2, and P3 had no significant effect (P>0.05) with control P0. The conclusion of this study was that the addition of eggshell flour at levels of 4%, 6%, and 8% in the ration could increase the slaughter weight, carcass weight, carcass percentage, and the physical composition of the meat portion of the carcass, but gave the same results to the bone percentage. and the percentage of fat including the skin of quail ( Coturnix-coturnix japonica ) aged 10 weeks. Keywords: Coturnix-coturnix japonica, carcass physical composition, egg shell